METHOD OF PATH CONSTRUCTING OF INFORMATION ROBOT ON THE BASIS OF UNMANNED AERIAL VEHICLE - Lysenko, Alexander; Tachinina, Olena (Proceedings of National Aviation University (archive), 2017)
Purpose: The purpose of this article is to present a method for constructing the branching path of the information robot (IR) that is a compound dynamic system (CDS) allowing us to formulate, in terms of optimal control theory, conditions of CDS path modeling with an arbitrary branching scheme. Methods: The article describes a method of theory of discontinuous dynamical systems optimal control, which is used to prove the optimality conditions for phase coordinates in the points of structural transformations of the IR’s branching path. Results: The necessary conditions for the optimality of the branching path along which the IR moves are defined. These conditions allow using standard subprograms to solve ordinary differential and algebraic equations and thereby to solve the task of modeling the optimal path of CDS with an arbitrary branching scheme. Discussion: The proposed method is the methodological basis for definition the computing algorithms allowing to simulate the optimal CDS paths. The proposed procedure of optimal branching paths simulating is part of the IR’s computer-aided design software and can be used to define computing algorithms taking into account the peculiarity of information-telecommunication interaction of CDS’s specific elements.